Cholangiocarcinoma-on-chip: A 3D liver tumor platform for personalized medicine. (March 2023) - Polidoro, M.A.; Saladino, G.; Ferrari, E.; Rasponi, M.; Marzorati, S.; Lleo, A.
Abstract : Intrahepatic cholangiocarcinoma (iCCA) is a deadly cancer of biliary epithelium with generally unsuccessful therapeutic options. This highlights the importance of deeper decipher iCCA mechanisms to develop new effective therapeutic strategies. Nevertheless, in-vivo cell interaction complexity has hindered an effective recapitulation of the in-vitro human milieu through 2D culture systems. In the last years, strong efforts were focused on the Organ-On-Chip (OoC) as promising models to faithfully recapitulate the in-vivo tumor niche. In this study, we aimed to develop an in-vitro 3D microfluidic device by co-culturing three cell types involved in iCCA. Primary iCCA cells were isolated from patients surgically resected at Humanitas Research Hospital. The microfluidic device was fabricated at Polytechnic of Milan, composed of three microfluidically interconnected channels. iCCA microenvironment was recapitulated by co-culturing iCCA cells and cancer-associated fibroblasts (CAFs) in the central channel with an ad hoc medium and embedded in an optimized hydrogel, flanked by an endothelial tubule in the lateral channel. The 3D cellular organization was visualized using confocal microscopy and the significant increase in the expression of key phenotypic cell markers was assessed by q RT-PCR, compared to 2D culture system. Diffusion assays at small and large molecules showed the high biocompatibility of this platform and the functional integrity of the endothelial tubule. Subsequently, the mechanical and biological proprieties of the platform were evaluated overtime in culture, showing that the cross-talk established between iCCA cells and CAFs within the chip led to a deep extracellular matrix remodeling. Indeed, scanning electron microscopy (SEM) allowed to measure the dimension of the matrix pores and immunofluorescence assay revealed a significant increase in the collagen IV deposition within the hydrogel. Our results showed that iCCA-on-chip provides a reliable 3D platform able to mimic the in-vivo iCCA microenvironment and may represent useful tool to investigate patient-specific therapeutic strategies.